Declining Premature Mortality From Major Noncommunicable Diseases During the COVID-19 Pandemic in Jakarta, Indonesia - Endang Indriasih; Tati Suryati; Ingan Ukur Tarigan; Selma Siahaan; Made Ayu Lely Surati; Anni Yulianti (Asia Pacific Journal of Public Health, 2026)
This study examined trends in premature mortality from major noncommunicable diseases (NCDs) among individuals aged 30 to 69 years in Jakarta, Indonesia, from 2016 to 2021, and assessed excess mortality during the COVID-19 pandemic. A population-based ecological analysis was conducted using mortality data from the Jakarta Provincial Health Office. Causes of death were classified using International Classification of Diseases, Tenth Revision and grouped into major NCD categories. Incidence rate ratios and excess mortality were estimated to compare pre-pandemic and pandemic periods. A total of 46 562 deaths were analyzed. Mortality increased during 2016 to 2019 but declined in 2020 to 2021. No significant differences in cause-specific mortality were observed, while overall mortality was higher in the pre-pandemic period. Excess mortality was negative across all major NCDs. Although mortality declined, this pattern should be interpreted with caution, as it likely reflects disruptions in reporting and health care access rather than a true reduction in disease burden.